Differences in Profits in MSMEs Before and After the Implementation ofe-Commerce : Case Study on Cornnah Home Industry - Nurinul Haq; Bahari, Bahari; Weka Gusmiarty Abdullah (International Journal of Technology and Education Research, 2024)
This research is motivated by the large number of MSMEs in Kendari City but it is still rare to implement a sales system through e-commerce even though utilizing the e-commerce platform can increase sales and profits and can reduce production costs. This research was conducted in Anaiwoi Village, Kadia District, Kendari City, Southeast Sulawesi. The purpose of this study was to determine how the application of e-commerce and how the difference in profits before and after the application of e-commerce in MSMEs The informants of this study were the owners of the Cornnah Home Industry This research uses descriptive methods and quantitative data analysis using paired sample test analysis using SPSS 26 data analysis tools. The results of the study obtained that the Cornnah household industry utilizes e-commerce platforms such as Shopee and Tokopedia and utilizes Instagram social media and digital transactions in helping the sales and marketing process of Cornnah corn chips products based on the results of a different test using a paired sample test showing that a significant value of 0.040 <0.05 which gives the conclusion that the application of e-commerce provides a difference in profits for Cornnah Household Industry business owners before and after the application of e-commerce